Starożytna symbolika morza i łodzi w wypowiedziach Ojców Kościoła - Wróbel, Ryszard (Vox Patrum, 2008)
The starting point of this article is to compare the sea and the life, which for people from the Mediterranean culture was something completely natural. Bearing in mind the numerous statements of the Fathers of the Church, we try to discover the source of such beliefs. We do this based on the three most popular marine allegories: the sea, the boat and ‘rescue board’, which stayed for good in patristic though. Because of the theme of the work we drew attention only to those elements which are obviously useful in better understanding of the patristic interpretation of the pericope about ‘Stilling of the Storm’. Special attention was given to the three groups of texts about: ‘boat of the State’, ‘boat of the soul’ and ‘boat of the world’, which could have a tangible influence on forming the thought of the Fathers of the Church associated with the symbolism of the Church boat. The way in which the Fathers of the Church use the complex symbols of Hellenist world shows theirs keen interest in current matters of the ordinary men and influence which faith rendered on their lives in the individual, as well as social dimension. The ancient symbolism inherent in the maritime assets in the context of patristic exegesis and constitutes an indelible part of theology of the original Church. The proper understanding is therefore of great importance for the correct interpretation of patristic writers’ views, particularly their views on the Church.